Hydrogen production on bimetallic catalysts and local acidity investigation of aluminosilicates and mesoporous silica via single molecule spectroscopy - Xie, Jingyi (Kansas State University, 2016)
The autothermal reforming and partial oxidation of hexadecane via Pt/Ni bimetallic nanoparticles on various ceria-based supports were investigated. Nanoparticles with Pt/Ni molar ratios ranging from 0/100 to 10/90 were loaded on ceria-based supports including cerium oxide, gadolinium-doped cerium oxide and cerium-doped zirconium oxide. The effect of the Pt/Ni molar ratio and the promotional effect of the support were studied by comparing the hydrogen yield. TPR and XPS analysis showed that there was a strong interaction between Ni and the CeO₂-ZrO₂ support, which led to enhancement of catalyst performance when the Pt/Ni ratio was low. The strong interaction between Ni and CeO₂-ZrO₂ support was induced by the formation of a solid solution between NiO and ZrO₂. In the case of bimetallic catalysts loaded on Gd₂O₃-CeO₂, no significant improvement in the catalytic activity of autothermal reforming was achieved until the Pt/Ni ratio reached 10/90. With C-snarf-1 as a pH-sensitive fluorescent probe, the local acidity on the surface of gradient aluminosilicate thin films and in the pore structure of mesoporous silicate films was explored. The single molecule emission ratio (I₅₈₀/I₆₄₀) of C-snarf-1 on the gradient aluminosilicate films showed similar results as previously reported for aluminosilicate mesoporous films. As the Al/Si ratio increases, the emission ratio declines, indicative of increased material acidity. In the case the mesoporous silicate films, much broader distributions of emission ratios were observed and are suggestive of significant heterogeneity in the pore structure of these films. The average emission ratio increased with a rise in pH until pH 6 or 7. A further rise in pH leads to a decline in emission ratio. Molecules with high mobility showed a narrow distribution and slightly lower average emission ratio when compared to data from all detected molecules. This observation implies a reduced heterogeneity for mesopores in which the molecules rapidly diffuse. The narrow distribution and lower average value of emission ratio at low pH, combined with the decrease in emission ratio induced by an increase in ionic strength may further indicate that the interaction between dye molecules and the pore surface impacts the emission ratio of the dye molecules.
Keywords: Hydrogen production; Bimetallic catalysts; Higher hydrocarbon; Local acidity; Single molecule spectroscopy; Mesoporous